Geological setting of the Moorowie Formation, lower Cambrian Hawker Group, Mt Chambers Gorge, eastern Flinders Ranges, South Australia. Issue 7 (2nd October 2020) - Mount, T. J.; Jago, J. B.; Langsford, N. R.; Dalgarno, C. R.
Abstract: Geological mapping in 1970 of lower Cambrian outcrop in the eastern Flinders Ranges of South Australia included the description and naming of the Moorowie Formation, representing the uppermost Hawker Group. The mapping is supported by 885 m of measured sections. An early Cambrian regressive-marine shelf-margin succession is described, from the massive Wilkawillina Limestone (base), the grey laminated limestones, syndepositional slump-induced intraformational folds and breccias, collapse talus, and graded sediment gravity flow deposits of the Mernmerna Formation, terrace-edge attrition megabreccias and reefs of the Moorowie Formation, passing up to the red beds of the Billy Creek Formation (top). Rapid changes in sedimentary facies are attributed to basement block movements and diapiric influence on sedimentation with abrupt vertical relief and paleoslope indicated by syndepositional slumping and platform margin collapse. Tuffs in the Mernmerna Formation record contemporaneous volcanism. Massive archaeocyathan limestones, ooid grainstones, peloid limestones, reef-sourced megabreccias and red shales define five members in the overlying Moorowie Formation, signalling shallow-marine regressive conditions and the development of a biologically diverse carbonate platform seaward of evaporitic lagoons and supratidal sabkhas. The megabreccias of the Moorowie Formation formed as thin semi-autochthonous debris aprons or shallow tidal-channel infills resulting from gradual and persistent wave attrition and repeated collapse of a carbonate terrace that was vigorously reworked by tidal currents. Shale interbeds within the Moorowie Formation represent lightly channelised shallow-marine ramp deposits, with adjacent mud flats, as easterly equivalents of the Oraparinna Shale, the earliest of which formed the substrate to the attrition megabreccias. Emergent evaporite diapirs near Mt John and Mt Frome are the probable sources of coarse siliciclastics within the carbonates. Some of the siliciclastics were likely transported onto the carbonate platform by sandstorms or migrating dunes. Late in the Cambro-Ordovician Delamerian Orogeny, earlier salt diapirs at depth were compressed and reactivated as highly mobile evaporite-rubble breccias and intruded as small plugs and dykes into fissures in a lithified and folded cover. The intrusive breccias include metasediment and metabasic xenoclasts attributable to the Callanna Group, while diapir-related faults also host minor copper, lead and barite mineralisation. Documentation of this unique record contributes to wider investigations of the Ediacaran-to-early-Cambrian succession of the Flinders Ranges sector of the Arrowie Basin, adding to its global heritage values, effective management and appreciation by the wider community.